The Ẓāhirīs : their doctrine and their history : a contribution to the history of Islamic theology - Goldziher, Ignác, 1850-1921 (Brill classics in Islam ;, 2008)
Ignaz Goldziher wrote his book ""Die Zahiriten"" in 1883. The English translation of this standard work on Islamic jurisprudence appeared in 1971. The book has been in print ever since. This new edition in the ""Brill Classics in Islam"" series shows that The Zahiris has not lost any of its actuality.